The efficacy of telemedicine interventions on quality of life and depression in individuals with spinal cord injury: a systematic review and meta-analysis - YinHu Tan; Xue Liang; Wei Ming; HuiMin Xing; Yan Liang; Yang Wang; Emmanuel Onyebuchi Onodu (Frontiers in Psychiatry)
ObjectiveThe purpose of this systematic review and meta-analysis is to examine the impact of telemedicine interventions on the quality of life (QoL) and depression in individuals with spinal cord injury (SCI).MethodsA literature search was conducted in four electronic databases (PubMed, Web of Science, EMBASE, and the Cochrane Library) from their inception to February 1, 2024. Two authors independently screened the studies and extracted the data. Cochrane’s bias risk tool for randomized controlled trials was used to examine the methodological quality of the included studies. A meta-analysis was conducted using Review Manager (version 5.4) to synthesize the results of the included studies.ResultsA total of 10 trials with 728 participants were included in the review. The results of the meta-analysis showed that telemedicine interventions significantly improved QoL [Standardized Mean Difference (SMD)=0.72, 95% Confidence Interval (CI) (0.11, 1.32), P=0.02] and reduced depression scores [SMD=-0.18, 95% CI (-0.31, -0.05), P=0.006].ConclusionsTelemedicine interventions are a feasible method to support people with SCI, and can mitigate depression and enhance quality of life. In the future, studies should involve larger sample sizes and extended follow-up periods to validate these findings and to identify the most effective telemedicine interventions for improving the overall health outcomes of individuals with SCI.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024508702.